Validity and reliability of prediction equations based on anthropometric indices to estimate body composition in athletes with an amputation - Rivera-Amézquita, L. V.; Saavedra-Bernal, X.; Escorcia-Gómez, D. C.; Ramos-Caballero, D. M. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: Body composition needs to be monitored in athletes with amputation because these parameters are related with their performance and health. The most common method of evaluation is the prediction equations based on anthropometric indices. However, they assume body symmetry; this is not the case of athletes with amputation. Consequently, the use of anthropometry and the prediction equations might not be adequate. Therefore, the aim of this study is to explore the validity and reliability of predictive equations based on anthropometric indices to estimate body composition in athletes with unilateral lower limbs amputation, compared with the gold standard Dual-energy X-ray absorptiometry (DEXA).